A Qualitative Exploration of the Use of Attachment Theory in Adult Psychological Therapy. (19th January 2015) - Burke, Eilish; Danquah, Adam; Berry, Katherine
Abstract : There is a growing interest into how attachment theory can inform psychotherapeutic practice with adults. This study aimed to explore how a group of therapists with an interest in attachment theory use it in their work with adult clients. A cross‐sectional qualitative design was adopted. Sampling, data collection and analysis procedures were guided by grounded theory principles. Semi‐structured telephone interviews were conducted with 12 therapists from a variety of training backgrounds. Data were coded and developed into thematic categories. Six primary themes were identified to describe how attachment theory influenced the clinical practice of the sample through the following: (i) complementing other therapeutic models; (ii) providing a framework to understand the development of clients' mental health problems; (iii) working with different attachment styles; (iv) thinking about the therapeutic relationship as an attachment relationship; (iv) influencing the different stages of the therapeutic process; and (vi) influencing clinical service design and delivery. It is concluded that attachment theory can play a significant role in influencing the practice of therapists and can be usefully adopted to complement therapeutic processes irrespective of the therapist's dominant clinical orientation. Further research is needed to explore the views of clinicians from different theoretical orientations and to investigate the security of the client–therapist attachment within the context of therapeutic change processes. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Message: Attachment theory may have implications for practice across a range of different types of therapy and may help therapists to bridge apparent differences between modality‐specific formulation and techniques. Attachment theory can be used to understand the development of mental health problems. Therapists should assess and formulate clients' attachment styles, and these formulations should guide therapeutic approaches. Attachment theory provides a comprehensive framework for facilitating the therapist's attentiveness to relational issues and use of the therapeutic relationship as a fulcrum for change. The principles of attachment theory can be used to inform all stages of the therapeutic process, as well as the design and delivery of mental health services.